Ethnopedagogical Approach in Multicultural Learning - Miftahul Jannah (Social Studies Education Department, Faculty of Teacher Training and Education, Universitas Lambung Mangkurat, 2022)
Indonesian people live in diversity, creating cultural wealth in society. However, the community's character, with different cultural patterns in each group, becomes vulnerable to conflict caused by discrimination and lack of tolerance. Therefore, efforts are needed to solve these problems, including through education based on local wisdom that can be applied in schools in the application of tolerance values ​​using an ethnopedagogical approach in multicultural learning with local wisdom related to knowledge generated, stored, applied, managed, and inherited. Create a more harmonious attitude and action. Multicultural-based learning is a reform movement that aims to create equal educational conditions for all students regardless of gender, race, religion, language, culture, or social status and foster tolerance, acceptance, respect, and affirmation of solidarity. Mastered by the concept of local wisdom values ​​that exist in the community, bringing students to have an understanding of social values ​​and have the skills to solve problems, live in harmony in society, respect the diversity of cultural characteristics of other individuals, and recognize and respect different cultures.